Designing for dissemination in chronic disease prevention and management - Owen, N.; Goode, A.; Sugiyama, T.; Koohsari, M.; Healy, Genevieve; Fjeldsoe, B.; Eakin, E. (Oxford University Press, 2017)
This chapter emphasizes the need for research that is designed and implemented explicitly with dissemination in mind. This is illustrated in relation to environmental and policy initiatives to influence physical activity through active transport, and through the example of initiatives to reduce workplace sitting. The other element of this chapter, the broad-reach intervention-dissemination case study of a health behavior-change program, highlights the need to maintain key elements of research quality in designing for dissemination, to the extent that is practically possible: a rigorous study design; the systematic tracking of implementation and related costs; and, the conduct of dose-response, maintenance and cost-effectiveness analyses. These examples of designing for dissemination illustrate not only the exciting opportunities for real-world dissemination research, but also the resourcefulness and commitment required for success.